Reassessing Twitter's Agenda-Building Power: An Analysis of Intermedia Agenda-Setting Effects During the 2016 Presidential Primary Season. (August 2018) - Conway-Silva, Bethany A.; Filer, Christine R.; Kenski, Kate; Tsetsi, Eric
This study examined the relationship between elite news media agendas and campaign agendas during the 2016 presidential primary season. Computer-assisted content analysis was used to assess issue emphasis within Twitter feeds of U.S. presidential primary candidates and their campaigns as well as the nation's top newspapers. The relationship between the overall Twitter agenda and that of newspapers, as well as the influence of front-runners Clinton, Cruz, Sanders, and Trump, was investigated using time series analysis. Aggregate and candidate-specific findings reveal some reciprocal relationships, but overall greater influence of newspapers on the Twitter agenda was detected. Findings suggest that Twitter has the potential to break free from and influence traditional media gatekeeping.